2016
DOI: 10.4012/dmj.2015-090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentin laser irradiation at different pulse settings on microtensile bond strength of flowable resin

Abstract: The aim of this study was to compare the effect of Er:YAG laser irradiation and adhesive systems on the microtensile bond strength (μTBS) of flowable resin to dentin. The flat dentin surfaces of 30 wisdom molar teeth were randomly divided into 3 groups (n = 10): no laser etching (control), laser etching using QSP and MSP modes. After the application of the flowable and the composite resin, and 5,000 thermal aging, the μTBS results were analyzed with two-way analysis of variance and Tukey's honest standard of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…Piyasaya sürülen bu ürünlerle, yapılacak olan post-kor restorasyonunda kullanılacak olan materyal sayısı azaltılarak, monoblok sistemin oluĢmasına katkıda bulunulması amaçlanmıĢtır. [17][18][19][20] Bu çalıĢmanın amacı, dentin ile yeni geliĢtirilen monoblok kor kompoziti arasındaki bağlanma dayanımına farklı Er:YAG lazer parametrelerinin etkisinin değerlendirilmesidir. ÇalıĢmanın hipotezi, Er:YAG lazer ile pürüzlendirilen dentin yüzeyi ile kor kompoziti arasındaki bağlanma dayanımının artacağıdır.…”
Section: Gġrġġunclassified
See 2 more Smart Citations
“…Piyasaya sürülen bu ürünlerle, yapılacak olan post-kor restorasyonunda kullanılacak olan materyal sayısı azaltılarak, monoblok sistemin oluĢmasına katkıda bulunulması amaçlanmıĢtır. [17][18][19][20] Bu çalıĢmanın amacı, dentin ile yeni geliĢtirilen monoblok kor kompoziti arasındaki bağlanma dayanımına farklı Er:YAG lazer parametrelerinin etkisinin değerlendirilmesidir. ÇalıĢmanın hipotezi, Er:YAG lazer ile pürüzlendirilen dentin yüzeyi ile kor kompoziti arasındaki bağlanma dayanımının artacağıdır.…”
Section: Gġrġġunclassified
“…Dentin yüzeyi ile lazer ucu arasındaki mesafeyi standardize etmek için lazer el aletine akrilik rezin yardımıyla iĢaretli bir frez adapte edildi. 20 Grup L2: Örneklerin dentin yüzeyleri grup L1'de anlatıldığı gibi lazer ile pürüzlendirildi. Lazer enerjisi 150 mj ve güç çıkıĢı 1.5 W olarak değiĢtirildi.…”
Section: öRneklerin Hazırlanmasıunclassified
See 1 more Smart Citation
“…[9][10][11] Although the bond strength of ER and SE adhesives to laser-ablated substrates was extensively tested in the literature, only a few studies evaluated the bonding performance of universal adhesives (UAs) to laser-ablated dentin using low or high powers. [12][13][14][15][16] Universal dental adhesives are known as "multi-mode" adhesives that can be applied in etch-and-rinse (ER), self-etch (SE), or selective-etching modes, depending on the clinical situation. Mild UAs proved their ability to achieve a significantly strong bond to dentin, which owes to the presence of functional monomers as a principal ingredient, which plays a major and unique role in chemical adhesion to dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Mild UAs proved their ability to achieve a significantly strong bond to dentin, which owes to the presence of functional monomers as a principal ingredient, which plays a major and unique role in chemical adhesion to dentin. 18,19 While few studies have reported no influence of the laser etching with low output power on the bond efficacy of some UA when used in either SE or ER modes, [12][13][14] other studies have found that this effect is material-dependent. 12 Furthermore, some studies have reported that LCM causes deterioration of the bond strength of UA.…”
Section: Introductionmentioning
confidence: 99%